Analisis Hukum Terhadap Tindakan Penghindaran Pajak (Tax Avoidance) Yang Dilakukan Oleh Perusahaan Berdasarkan Hukum Pajak Di Indonesia - Fauzan Zaki; Budiman Ginting; Tengku Keizerina Devi; Chairul Bariah (USU LAW JOURNAL, 2019)
Abstract. Tax avoidance as an effort to alleviate the tax burden by not violating existing laws. Although there is no law that is violated, all parties agree that tax avoidance is not acceptable. This is because tax avoidance directly results in reduced state revenues. The problem in this thesis is whether tax avoidance actions carried out by company management violate the rule of law, what is the responsibility of company management if there are findings from the Directorate General of Taxes on corporate tax avoidance that lead to corporate tax evasion and what are the legal consequences for avoidance actions atas. The research method is carried out in a normative juridical manner. The nature of this thesis research is descriptive. Data sources are primary, secondary and tertiary legal materials. Data collection techniques were carried out with subsequent library research conducting interviews and then the data were analyzed qualitatively, so that later the results of this study would be deductively concluded. Based on the research conducted, it was concluded that tax avoidance actions carried out by company management violated the rule of law in an effort to reduce the tax burden. Taxpayers or business entities often take advantage of applicable loopholes. This happens because of the gap in legislation that can be utilized by the taxpayer to reduce the tax burden in question. The responsibility of the management of the company if there are findings of the results of the Directorate General of Taxes on corporate tax avoidance which leads to corporate tax evasion in the form of directors or commissioners that have been stated in the articles of association of a corporation. Directors and commissioners can be held accountable for criminal matters in the case of corporate crime. The involvement of directors or commissioners in criminal acts committed by corporations, where this is reflected in the presence of malicious intent (mens rea) and bad deeds (actus reus) carried out by the board of directors or commissioners. The legal consequences for companies for tax avoidance measures are taxation sanctions for tax avoidance actions and loss of company reputation. the company does not operate and or does not operate as expected.   Keywords: companies, tax avoidance, embezzlement